Spawning Potential Ratio of Feather Back (Chitala Lopis) at Kampar River, Riau - Andri Warsa; Endi Setiadi Kartamihardja; Arif Wibowo (Journal Omni-Akuatika, 2018)
The feather back, Chitala lopis is an important economic fish, inhabit Kampar River and its population tend to decrease so that management and conservation efforts should be conducted.  Limited data of the feather back is one of the problems in formulating the management of the population. Spawning potential ratio (SPR) approach is an option being used in the management of the fish stock in the poor data. The study aimed to analysis spawning potential ratio of the feather back in Kampar River, Riau. The research has been conducted in May, August and October 2016. The total length at first capture (Lc) of feather back was less than the total length at first maturity (Lm) with the SPR value of 5 %. This condition could impact to decreasing the feather back stock. The SPR value should increased more than 20 % so the feather back population would been stable. Regulation of the fisheries was mainly limited mesh size of the gillnet operated should be applied.